2020
DOI: 10.1096/fj.202000826r
|View full text |Cite
|
Sign up to set email alerts
|

LINGO family receptors are differentially expressed in the mouse brain and form native multimeric complexes

Abstract: Leucine‐rich repeat and immunoglobin‐domain containing (LRRIG) proteins that are commonly involved in protein‐protein interactions play important roles in nervous system development and maintenance. LINGO‐1, one of this family members, is characterized as a negative regulator of neuronal survival, axonal regeneration, and oligodendrocyte precursor cell (OPC) differentiation into mature myelinating oligodendrocytes. Three LINGO‐1 homologs named LINGO‐2, LINGO‐3, and LINGO‐4 have been described. However, their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…( 38 ) Neither TFF3 nor TFF3 homodimer displayed any effect on LINGO2 dimerization, which was assessed by BRET ( Figure 3 E). 59 Due to the limited availability of functional LINGO2 bioassays, we cannot fully exclude that TFF3 does not signal through LINGO2 and we can only state that TFF3 does not interfere with LINGO2 dimerization.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…( 38 ) Neither TFF3 nor TFF3 homodimer displayed any effect on LINGO2 dimerization, which was assessed by BRET ( Figure 3 E). 59 Due to the limited availability of functional LINGO2 bioassays, we cannot fully exclude that TFF3 does not signal through LINGO2 and we can only state that TFF3 does not interfere with LINGO2 dimerization.…”
Section: Discussionmentioning
confidence: 93%
“…No ligand able to alter LINGO2 dimerization is known; therefore, no positive control could be used. 59 Results are expressed as mean ± SEM for n = 4. One-way ANOVA followed by Dunnett correction was performed to assess differences between treated and nontreated cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lingo1 loss-of-function promotes axon regeneration and neuronal survival in various CNS injury and disease models (Fu et al, 2008; Inoue et al, 2007; Ji et al, 2006). A recent study showed that Lingo family receptors could form heteromers with one another in the mouse brain (Guillemain et al, 2020), suggesting potential functional overlap between the paralogs. Tenascin-R is an extracellular matrix molecule that was shown in previous studies to be a repulsive guidance cue in zebrafish during development (Becker et al, 2003) and an inhibitor of mouse optic nerve regeneration (Becker et al, 2000).…”
Section: Discussionmentioning
confidence: 99%